Analisis Penggunaan Alokasi Dana Desa (ADD) dalam Kegiatan Pemberdayaan Masyarakat di Desa Pagersari Kecamatan Bergas Kabupaten Semarang - Afifah Rachmadeva Amartha; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Based on the Regulation of the Minister of Domestic Affairs Number 37 of 2007, the source of village finances from the Village Fund Allocation (ADD) is used to finance the empowerment of the community by 70% of the total acceptance of ADD in each village. Desa Pagersari is a village that has not reached the limit of using ADD to finance community empowerment by 70% and community empowerment programs that do not yet meet community needs. The purpose of this study is to analyze the use of ADD to community empowerment program based on Semarang Regions No. 1 of 2016 and to know the obstacles of ADD use in the community empowerment program of Pagersari village. This type of research is descriptive research using a qualitative approach. The results of the study showed that in analyzing the use of ADD towards community empowerment programs, it was still not right from the aspect of the principle of ADD management, namely transparency and participatory; ADD compatibility which is an integral part of the Village Revenue and Expenditure Budget from planning, implementation to accountability; The use of ADD is 70% for community empowerment spending. Factors inhibiting the use of ADD to the community empowerment program that is the compliance factor of the applicant on the applicable provisions; people who are still passive. Recommendations given the need for communication between policy implementers and the community in meeting the needs of the community, it is necessary to do commitment education for policy implementers in order to maximize their duties, need to adjust the target of the empowerment program and the nature of program sustainability.